Drivers and pathways of NPD success in the marketing–external design relationship - Hemonnet-Goujot, Aurélie (2019)
Marketing often cooperates with external design in the new product development (NPD) process. While this relationship is crucial for NPD success and is a typical case of interorganizational collaboration between a business-oriented function (marketing) and a creative partner (external design), a comprehensive understanding of this relationship remains lacking. As the NPD field evolves to open systems that have changed concepts like functional integration into interorganizational integration, this study contributes to NPD literature by developing an integrated conceptual framework leading to a model of drivers and pathways of NPD success in the marketing–external design relationship. Building on the literature on NPD, design management and relationship marketing, and on nine dyadic case studies from the luxury fragrance and cosmetics industry, a content analysis was conducted, enriched by a crisp-set qualitative comparative analysis (QCA). This research confirms several NPD success drivers suggested in the literature and reveals three new drivers: source of design expertise, designer brand commitment, and number of NPD stages involving designer. The first new driver (source of design expertise) impacts the relationship process, which then impacts NPD success, while the other two drivers (designer brand commitment, and number of NPD stages involving designer) directly influence NPD success. The paper also identifies the pathways of NPD success, showing that contact authority and designer brand commitment are necessary conditions for NPD success, especially when combined with a high number of NPD stages involving designer or a previous relationship. The results also indicate that pathways of NPD success may differ according to the source of design expertise. From a managerial perspective, this study provides recommendations to managers to select the right design partner and choose from a range of drivers and pathways to devise more effective ways to work with external designers, thereby leading to NPD success.